Molecular dissection of large cell carcinomas of the lung with null immunophenotype - Harms, Alexander; Endris, Volker; Winter, Hauke; Kriegsmann, Mark; Stenzinger, Albrecht; Schirmacher, Peter; Warth, Arne; Kazdal, Daniel (Pathology, 2018)
Summary - The aim of this study was to subcategorise large cell carcinoma (LCC) with null immunophenotype according to the World Health Organization (WHO) Classification of 2015 into the existing groups of adenocarcinoma and squamous cell carcinoma by further molecular genetic analysis. Lineage-specific molecular alterations of these tumours could depict additional therapeutic approaches. We analysed a cohort of 35 LCC diagnosed according to the 2004 WHO classification and reclassified them according to the criteria of the 2015 WHO classification. Subsequently, tumours with a null immunophenotype were analysed by targeted next generation sequencing (42 marker genes including TP53, EGFR, KRAS, STK11 and SMARC4A) and fluorescence in situ hybridisation (ROS1, ALK). By applying the criteria of the 2015 WHO classification and subsequent molecular subtyping we could show that out of 35 previously diagnosed LCC, 16 cases could be reclassified into specific NSCLC subtypes using immunohistochemistry. Additionally, based on their mutational pattern, eight of the remaining 19 cases with null immunophenotype could be assigned as ‘favour adenocarcinoma’. We demonstrate that molecular subtyping is helpful to further categorise LCC with null immunophenotype. Our findings argue for an algorithm including stratified molecular analysis of all respective cases.
Gesehen am 26.08.2019